How PETE comes to matter in the performance of social justice education. (3rd September 2018) - Ovens, Alan; Flory, Sara B.; Sutherland, Sue; Philpot, Rod; Walton-Fisette, Jennifer L.; Hill, Joanne; Phillips, Sharon; Flemons, Michelle
ABSTRACT: Background : For over four decades, there have been calls for physical education (PE) and physical education teacher education (PETE) to address social inequality and foster social justice. Yet, as numerous studies demonstrate, attempts to educate for social justice in PETE are infrequent and rarely comprehensive. This raises the question why it appears to be possible in some situations but not others, and for some students and not others. Purpose : The purpose of this paper is to examine the multiple socio-political networks or assemblages in which PETE is embedded and explore how these shape the possibilities for students to engage with the concept of social justice and sociocultural issues (SCI) when learning to teach PE. Two research questions guided this study: How does an orientation for social justice education (SJE) within education policy affect the standards for enacting PETE programs? How is SJE encouraged within PETE programs? Methodology : Drawing from a broader study of over 70 key personnel in more than 40 PETE programs, we examined how faculty in PETE understand their professional world, identify their subjective meanings of their experiences, and address SCI andSJE within PETE. Data sources included an initial survey, a semi-structured interview, and program artifacts. We analyze the ways that SJE/SCI was represented in three national settings (England, the United States, and New Zealand) and identified common themes. Results : Examination of each national setting reveals ways that SJE and SCI were enabled and constrained across the national, programmatic, and individual level in each of the countries. The coherence of explicit National policy and curricula, PETE program philosophies, and the presence of multiple individual interests in social justice served to reify a sociocultural agenda. Conversely, possibilities were nullified by narrow or general National Standards, programs that failed to acknowledge sociocultural interests, and the absence of a critical mass of actors with a socio-critical orientation. These differences in assemblage culminated in variations in curriculum time that served to restrict or enable the breadth, frequency, and consistency of the messages surrounding SCI in PETE. Conclusion : These findings highlight the importance of acknowledging socio-political networks where PETE operates. The agency of PETEs to enact pedagogies that foreground sociocultural interests is contingent on congruity of the networks. The authors caution that although the 'perfect storm' of conditions has a profound influence of the possibility of transformational learning of SCI in PETE, this arrangement is always temporary, fluid, and subject to changes in any of the three network levels. Additionally, the success of PETE in enabling graduating PE teachers to recognize the inequities that may be reinforced through the 'hidden curriculum' and to problematize the subject area is contingent on the expectations of the schools in which they teach.